PENGARUH INSENTIF DAN IKLIM ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN WINSTAR HOTEL PEKANBARU - Adzra, Tiara Nabilla; Andini, Frini Karina (Komunitas Manajemen Kompetitif, 2025)
This research aims to analyze the influence of incentives (X1), organizational climate (X2), on employee productivity (Y) Winstar Hotel Pekanbaru. The research method used in this research is a quantitative method by distributing questionnaires to Winstar Hotel Pekanbaru employees. The data analysis technique used is multiple linear regression analysis using SPSS version 20. Based on the results of the partial analysis, incentives have no effect on the productivity of Winstar Hotel Pekanbaru employees, this is because the tcount obtained is greater than the ttable value (1.789>2.0345). Organizational climate influences Winstar Hotel Pekanbaru employee productivity, this is because the tcount value obtained is greater than the ttable value (4.933>2.0345). Meanwhile, the F test shows that there is a simultaneous relationship between variables X and Y because Fcount is greater than the Ftable value (65,348>3.28) Keywords: incentives, organizational climate, productivity